The Analysis of citizens' preferences for energy investment alternatives in Turkey: Nuclear versus renewable energy - Akyazı, Pınar Ertör. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
Climate change and energy security are the two central issues in today’s energy policies. Two main policies are increasingly considered as the way to deal with these issues: Expansion of nuclear energy and a greater reliance on renewable energy sources. Turkey, as a developing country with a growing population and economy, is facing a rapidly rising energy demand and carbon emissions, and is therefore confronted with a similar policy choice in relation to its future energy path. On the one hand, since the country has huge economic potential of renewable energy sources, the expansion of renewables is suggested as the “green” alternative. On the other hand, the government is focusing strongly on the nuclear energy with connotations of “technological advancement”, “modernization” and “prestige” for the country. However, how the public perceives these two alternatives has not been questioned by the energy policy makers yet. In fact, this should clearly be an element of the policy-making, given the fact that economic, environmental and social costs of the chosen energy path are to be borne heavily by the households. This constituting our motivations, this study aims to provide the necessary insights into the nuclear versus renewable energy debate in the context of a developing country with rising energy needs by analyzing citizens’ preferences and their determinants for these two energy investment alternatives through a survey administered to 2422 respondents representative of urban Turkey. The findings demonstrate that there is large support for renewable energy sources, such as wind and solar, and that this support decreases only slightly even if electricity prices are to rise due to a wider utilization of these sources. Nuclear energy, on the other hand, is likely to be resisted by a large group of respondents with less techno-scientific optimism. Yet, knowledge of climate change increases the likelihood of support for both renewable and nuclear investments, whereas environmental concern is most likely to lead to persistent support for renewable energy sources. The results of the study are hoped to provide inputs for energy restructuring/reform in Turkey and in other countries with similar characteristics.
Keywords: Clean energy investment.; Renewable energy sources.